2015
DOI: 10.1021/acs.langmuir.5b01574
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations on Coalescence and Non-coalescence of Conducting Droplets

Abstract: When an electric field with various strengths is applied to two adjacent conducting droplets, the droplets may completely coalesce, partially coalesce, or bounce off one another. To reveal an atom-scale mechanism of coalescence or non-coalescence, dynamic behaviors of two conducting nanodroplets at a homogeneous electric field are studied via molecular dynamics simulations in this work. The results show that there is a critical field strength and a critical cone angle above which the two droplets partially coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(69 citation statements)
references
References 26 publications
0
69
0
Order By: Relevance
“…Recently, Ristenpart et al [10] experimentally found that full coalescence and partial coalescence can occur for any oil/water or gas/ water system. Furthermore, MD simulations on the electrocolescence of two droplets surrounded by nitrogen gas under constant DC electric field reproduced the phenomena observed in macroscopic experiments [14]. Therefore, the nitrogen/water system is adopted in the present MD simulations for saving computational time.…”
Section: Simulation Model and Methodsmentioning
confidence: 56%
See 3 more Smart Citations
“…Recently, Ristenpart et al [10] experimentally found that full coalescence and partial coalescence can occur for any oil/water or gas/ water system. Furthermore, MD simulations on the electrocolescence of two droplets surrounded by nitrogen gas under constant DC electric field reproduced the phenomena observed in macroscopic experiments [14]. Therefore, the nitrogen/water system is adopted in the present MD simulations for saving computational time.…”
Section: Simulation Model and Methodsmentioning
confidence: 56%
“…The reason of the partial coalescence was speculated to be charge transfer between the two droplets [12]. Recently, Wang et al [14] have corroborated this mechanism from atomic scale via molecular dynamics (MD) simulations.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…The water molecules are characterized by the SPC/E model with an O-H bond distance of 1.0 Å and a H-O-H angle of 109.47 • . 28 The intermolecular interactions of particles for the whole system are expressed as a combination of 12/6 Lennard-Jones and Coulombic potentials, and total potential energy can be obtained as following:…”
Section: B Potential Functionmentioning
confidence: 99%